2022
DOI: 10.1002/1878-0261.13295
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the spectrum of trivalent VAV1‐mutation‐driven tumours using a gene‐edited mouse model

Abstract: Mutations in the VAV1 guanine nucleotide exchange factor 1 have been recently found in peripheral T cell lymphoma and nonsmall‐cell lung cancer (NSCLC). To understand their pathogenic potential, we generated a gene‐edited mouse model that expresses a VAV1 mutant protein that recapitulates the signalling alterations present in the VAV1 mutant subclass most frequently found in tumours. We could not detect any overt tumourigenic process in those mice. However, the concurrent elimination of the Trp53 tumour suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Using a GEMM approach, Fukumoto et al [108] demonstrated that the ectopic expression of Vav1 gain-of-function mutations, Vav1 (165-174del) and Vav1-STAP2, leads to the development of T cell lymphomagenesis only when tumor protein P53 (TP53), a tumor suppressor gene is deleted [108]. In a similar study, Robles-Valero et al [117] showed in a gene-edited mouse model that the trivalent functional subclass of Vav1 mutations plays critical roles in the development of AITL, yet it requires the elimination of the suppressor activity of TP53. It is possible that the requirement for loss of TP53 is related to issues such as overcoming the negative selection that is probably imposed on thymocytes expressing active versions of Vav1.…”
Section: Vav1 and Genetically-engineered Mouse Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…Using a GEMM approach, Fukumoto et al [108] demonstrated that the ectopic expression of Vav1 gain-of-function mutations, Vav1 (165-174del) and Vav1-STAP2, leads to the development of T cell lymphomagenesis only when tumor protein P53 (TP53), a tumor suppressor gene is deleted [108]. In a similar study, Robles-Valero et al [117] showed in a gene-edited mouse model that the trivalent functional subclass of Vav1 mutations plays critical roles in the development of AITL, yet it requires the elimination of the suppressor activity of TP53. It is possible that the requirement for loss of TP53 is related to issues such as overcoming the negative selection that is probably imposed on thymocytes expressing active versions of Vav1.…”
Section: Vav1 and Genetically-engineered Mouse Modelsmentioning
confidence: 98%
“…The contribution of wild-type Vav1 [114][115][116] or Vav1 mutants [108,117] to tumor development has been studied in vivo recently, using genetically engineered mouse models (GEMMs). Expression of wild-type Vav1 in specific organs, such as the lungs [114] or the pancreas [116], indicated that while expression of Vav1 only did not lead to tumor development, co-expression of Vav1 with mutant K-Ras (K-Ras G12D /Vav1 mouse) synergistically enhanced tumor development in these organs [114,116].…”
Section: Vav1 and Genetically-engineered Mouse Modelsmentioning
confidence: 99%
“…The contribution of wild-type VAV1 [81][82][83] or VAV1 mutants [110,111] has recently been studied in vivo using GEMMs, as detailed below.…”
Section: Vav1 and Genetically-engineered Mouse Models (Gemms)mentioning
confidence: 99%
“…This pro-tumorigenic effect engages both the GEF-dependent and GEF-independent activities of VAV1 mutants [108]. In a gene-edited mouse model, Robles-Valero et al [111] showed that the trivalent functional subclass of VAV1 mutations plays a critical role in the development of AITL when the suppressor TP53 is inactive. The requirement for the loss of TP53 may be related to problems such as overcoming the negative selection likely imposed on thymocytes expressing the active version of VAV1 [111].…”
Section: Vav1 and Genetically-engineered Mouse Models (Gemms)mentioning
confidence: 99%
See 1 more Smart Citation